Media Representations of Speech Disorders in Characters from Selected Films for Children - Łangowska, Paulina (Przegląd Badań Edukacyjnych (Educational Studies Review), 2024)
Research so far shows that animated films are present in children’s lives from an early age. Young audiences are looking for role models, which often take the form of characters from animated films. The aim of the research presented in this article was to reconstruct media representations of speech disorders specific to characters in selected animated films aimed at children. The author used archive searching as a data collection method and content analysis as a method to analyse the collected material. The paper presents results of a speech disorder analysis of 18 children from Poland. Research shows that the most common speech disorder in animated films is lisping, followed by rhotacism and pararhotacism; there is also a relationship between animated characters’ speech disorders and their charakcter traits.